Breaking the Shackles of Kompeni Contracts: A Reflection of Butonese-Dutch Relations in a Letter from Vereenigde Oostindische Compagnie to Sultan Azimuddin - S., Suryadi (Malay Literature, 2018)
The Sultanate of Buton, situated in the south-eastern peninsula of Sulawesi Island, was an archipelagic Islamic kingdom that has long been existed before the arrival of European power in the Malay-Nusantara world. Politically, the Sultanate of Buton, that was relatively small, always feels threatened because of the territorial expansion and political rivalry between its large and powerful neighboring kingdoms: Gowa and Ternate. Therefore, the 4th Butonese sultan Dayanu Ikhsanuddin or La Elangi (1578-1615) pledged "everlasting alliance" with the Vereenigde Oostindische Compagnie (VOC) on 5 January 1613. The essence of the treaty was that the VOC would help Buton if attacked by the enemies, but with some requirements that must be met by Buton. The treaty had "bundled" the next Buton sultans. This paper discusses a 13-pages letter sent by the VOC's Governor in Makassar, represented the VOC's Governor General in Batavia, to the 25th Butonese sultan Azimuddin or La Masalumu (1788-1791), dated on 25 February 1791,which its digital version owned by The British Library under code EAP212/6/3 and its original manuscript hold in Abdul Mulku Zahari's collection in Baubau, Buton. This paper provides the Roman transliteration of the letter, discusses its contents and relates them to the socio-political historical background of the sultanate of Buton of that period. Keywords: Buton, letter, EAP212/7/3, The British Library, VOC, political contract, Sultan Azimuddin, colonialism